The first experience of surgical treatment of acute aortic dissection (type A) through the upper middle J-shaped ministernotomy - V. V. Vayda; I. I. Zhekov; V. I. Kravchenko; I. M. Kravchenko; O. B. Larionova; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2018)
In recent years, minimally invasive access has increasingly been implicated in cardiac surgery. Already there are many reports in Ukraine about the use of ministernotomy for correction of isolated aortic defects, as well as in conjunction with an ascending aortic aneurysm. These techniques are worked out and actively used. Despite the significant progress and development in this field, cases of surgical treatment of acute aortic dissection (type I for De Bakey) in Ukrainian literature we did not meet.To present a clinical case of surgical treatment of acute aortic dissection type A through the upper middle J-shaped ministernotomy. A patient, 28 years old, with a diagnosis of acute aortic aneurysm dissection type A, who undergone supracoronary replacement of the ascending aorta with hemiarch reconstruction under conditions of deep hypothermia and selective antegrade cerebral perfusion through the upper middle J-shaped ministernotomy.Thus, minimally invasive access, despite some technical difficulties, and taking into account the volume and complexity of surgical intervention, eliminates the disadvantages that are characteristic of the traditional longitudinal median sternotomy.